METAFISIKA SERAT JATIMURTI - Joko Siswanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2010)
AbstractThis article raises “Serat Jatimurti” as a systematic philosophy with a formal object: ontology. This article shows that: first, “Serat Jatimurti” maintains unity of beings autonomous. Individual beings is not it each him, but an elementary unity and binding in unity. Second, metaphysics of “Serat Jatimurti” have jetty at real world, but in multifarious of being there one ground of being as a being, that is Pure Reality was so-called “Kahanan jati” (Real Being). Third, the Real Being is a fundamental idea of metaphysics of “Serat Jatimurti”. All their metaphysics are instructed and concentrated on the Real Being: there is nothing, only Allah, that is being which is in fact referred as ‘Kahanan Jati”.Fourth, “Serat Jatimurti” differentiates the existence into fourstrata of being that is “garis, lumah, jirim and kajaten”. The four strata of being are ontological structure of entire reality that is one unity and a bundle of relationship. To comprehend it, hence, human should have dimensions of the four strata. Integration of the four dimensions in awareness, hence, human will be able to catch the overall reality. In this case there is attachment between human being and fact, subject-object.Keywords: ontology, beings, Real Being, four strata.